A Meeting with Blue Henry: Sputum Flasks and Cups and Tuberculosis Prevention - McGowan, Rowena (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2024)
The increasing acceptance of germ theory triggered a dramatic shift in both medical treatment of tuberculosis and its cultural perception. One of the consequences of this change was the introduction of the sputum flask or cup. Though simple, a sputum flask’s design and use reveal a great deal about early 20th century disease prevention beliefs, as well as the tension between germ containment and fears of marking oneself as infected. This paper explores the theories behind sputum flasks and the realities of their usage through contemporary writings and artifacts held by the Museum of Health Care at Kingston.